Imposing Policy on Reluctant Actors: The Hospital Desegregation Campaign and Black Postneonatal Mortality in the Deep South - Anderson, D. Mark; Charles, Kerwin Kofi; Rees, Daniel I. (The Review of Economics and Statistics, 2024)
In 1966, Southern hospitals were barred from participating in Medicare unless they discontinued their longstanding practice of racial segregation. Using data from five Deep South states and exploiting county-level variation in Medicare certification dates, we find that gaining access to an ostensibly integrated hospital had no effect on Black postneonatal mortality. Similarly, there is little evidence that the campaign contributed to the trend towards in-hospital births among Southern Black mothers. These results are consistent with descriptions of the hospital desegregation campaign as producing only cosmetic changes and illustrate the limits of anti-discrimination policies imposed upon reluctant actors.